[Opening of the Pampanga literature exhibit held at the Filipiniana Serials on September 25, 2000] (University Library, U.P. Diliman, 2000)
A recording of the program opening the Pampango Literature exhibit at the Filipiniana Serials section of the UP Main Library on Sept. 25, 2000.